3D printed high oil custard cream: Effects of whey protein isolate, hydroxypropylated starch and carrageenan on physicochemical properties and printing performance. (15th February 2022) - Cai, Qingying; Zhong, Yinglin; Xu, Meiling; Huang, Qingrong; Lu, Xuanxuan
Abstract: 3D printing of ready-to-eat emulsion-based food product with high liquid oil content is challenging due to the difficulty to formulate different ingredients as homogenous material with desirable rheological properties and good stability. This study established a high oil content custard cream-based 3D printing food and investigated the effect of whey protein isolate (WPI), hydroxypropylated starch and carrageenan ratios on the physiochemical properties and printing performance of custard cream. Different ratios of WPI (0–6.0 wt%), hydroxypropylated starch (0–6.0 wt%), and carrageenan (0.05–2.0 wt%) were used to prepare custard cream with oil content of 20.0 wt%. Low field nuclear magnetic resonance study indicated that water distribution in custard cream with WPI/hydroxypropylated starch ratio of 3:2 and carrageenan content of 0.5% was more homogenous than other samples. The carrageenan content exhibited a larger influence on rheological and textural properties of custard cream than WPI and hydroxypropylated starch. Microstructure study suggested that all custard cream were stable oil-in-water emulsion formulations after storage of one month. Custard cream prepared with total WPI/hydroxypropylated starch content of 3%–6% and carrageenan content of 0.5% was desirable for extrusion-based 3D printing. The results from this study would facilitate the development of emulsion-based ready-to-eat food products with 3D printability. Highlights: Custard cream with high oil content of 20% was fabricated. Role of WPI, modified starch and carrageenan on 3D printed custard cream was revealed. Physiochemical properties and printing performance of custard cream were evaluated.